2023
DOI: 10.5694/mja2.51870
|View full text |Cite
|
Sign up to set email alerts
|

The association between child maltreatment and mental disorders in the Australian Child Maltreatment Study

Abstract: Objectives: To examine the associations between experiences of child maltreatment and mental disorders in the Australian population.Design: Population-representative survey conducted by computerassisted telephone interviewing.Setting, participants: Australian residents aged 16 years and older.Main outcome measures: Mental disorder diagnoses of lifetime major depressive disorder, current alcohol use disorder (mild, moderate and severe), current generalised anxiety disorder and current post-traumatic stress diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…This knowledge is essential to develop evidence‐informed child protection policies, prevention strategies and interventions. Analysis of multi‐type maltreatment also enables assessment of its associations with mental health disorders, health risk behaviour and service use data, which are reported elsewhere in this supplement 26‐28 . Forthcoming analyses will examine differences in associated outcomes attributable to variability in age of onset, developmental periods of victimisation, chronicity, and particular multi‐type maltreatment combinations.…”
Section: Discussionmentioning
confidence: 99%
“…This knowledge is essential to develop evidence‐informed child protection policies, prevention strategies and interventions. Analysis of multi‐type maltreatment also enables assessment of its associations with mental health disorders, health risk behaviour and service use data, which are reported elsewhere in this supplement 26‐28 . Forthcoming analyses will examine differences in associated outcomes attributable to variability in age of onset, developmental periods of victimisation, chronicity, and particular multi‐type maltreatment combinations.…”
Section: Discussionmentioning
confidence: 99%
“…Mental disorders and substance use during adolescence can also influence the impact of maltreatment history on health service use in adulthood. The ACMS found associations between child maltreatment and mental disorders that emerged during early adulthood 17 . A prospective cohort study in the United States, with data collected at four time points, similarly found that the relationship between child maltreatment and increased health service use was partly explained by the increased risk of developing mental disorders; maltreated people with major depression or who used drugs during young adulthood (approximate age at follow‐up, 29 years) were significantly more likely to use general medical services in middle adulthood (approximate age at follow‐up, 41 years) 9 …”
Section: Discussionmentioning
confidence: 99%
“…The high prevalence of ACEs is a major public health concern that negatively affects development and increases the risk of mental health conditions and chronic diseases in later life (Gardner et al, 2019 ; Hughes et al, 2017 ; Scott et al, 2023 ). A systematic review by Petruccelli et al ( 2019 ), which included 96 articles on health outcomes associated with ACEs, showed that ACEs were associated with significantly poorer medical health outcomes, such as respiratory disease, ischemic heart disease, sleep problems, gastrointestinal disease, and somatic pain.…”
Section: Introductionmentioning
confidence: 99%